Effect of Glass Powder on Durability Performance of Hardened Concrete in Aggressive Environment - Odero, Frank Onyango; Omondi, Benard; Wamalwa, Chrispinus (Andalasian International Journal of Applied Science, Engineering and Technology, 2023)
Supplementary Cementitious Materials have been widely researched for application in concrete works, primarily to reduce dependence on cement as a binding medium. This research sought to add to that knowledge base by determining the effect of crushed waste glass powder on the durability performance of hardened concrete in an aggressive environment. Crushed waste glass powder was added to the concrete mix at 10%, 20% and 30% respectively by weight of cement. Fresh concrete was subjected to slump test while hardened concrete was subjected to compressive strength, water absorption, sulphate attack and electrical resistivity tests. The results were then compared to the control mix as well as previous studies. Optimal results were obtained at 30% addition of crushed waste glass powder into the concrete mix, noting an increase in compressive strength by 32.5%, water absorption reduced by 5.9%, sulphate attack effect was low while electrical resistivity reduced by 14.7%. Keywords: Absorptivity, Crushed Waste Glass, Durability, Electrical Resistivity, Pozzolanic Activity, Sulphate Attack.